2021
DOI: 10.1021/acs.analchem.1c03401
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Fluorescence Solvatochromism To Resolve Cellular Polarity upon Protein Aggregation

Abstract: Common solvatochromic fluorophores exhibit a bathochromic fluorescence emission wavelength shift accompanied by intensity attenuation due to the presence of nonradiative decay pathways at the excited state. Such intrinsic but inevitable fluorescence quenching of solvatochromism impedes its applications to faithfully quantify local polarity, especially in a polar environment. Herein, we report a new donor-π-acceptor (D-π-A) type solvatochromic fluorophore scaffold containing a perfluorophenyl group that exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…The same is true of the computed ground state dipole moments: for 1-4 these are somewhat lower than for other highly solvatochromic dyes: g values for Prodan, Nile Red, and NBD are approximately 4, 8, and 9 D, respectively [26] [27,28]. However, it is also true that more solvatochromic dyes also tend to have longer wavelength absorption maxima, lower quantum yields, and lower photostability [43]. Thus striking a balance among these features is key to the utility of a dye.…”
Section: Discussionmentioning
confidence: 98%
“…The same is true of the computed ground state dipole moments: for 1-4 these are somewhat lower than for other highly solvatochromic dyes: g values for Prodan, Nile Red, and NBD are approximately 4, 8, and 9 D, respectively [26] [27,28]. However, it is also true that more solvatochromic dyes also tend to have longer wavelength absorption maxima, lower quantum yields, and lower photostability [43]. Thus striking a balance among these features is key to the utility of a dye.…”
Section: Discussionmentioning
confidence: 98%
“…Based on the residual problem of photosensitizers in the body after photodynamic therapy, Huang et al designed and synthesized an AIE photosensitizer that can achieve self-degradation after treatment. 23,24 In this work, self-degradable conjugated CP1 was obtained by alternately assembling AIE molecules with imidazoles (Fig. 3a).…”
Section: Types and Mechanisms Of Photodynamic Therapymentioning
confidence: 99%
“…Panels of different non-covalent probes and sensors have been designed to illuminate the complex misfolded and aggregated conformations, including unfolded proteins, misfolded oligomers, amyloid aggregates, and amorphous aggregates. Compared with the non-covalent probes targeting aggregated proteins, covalent probes were still underdeveloped due to the lack of chemical strategies to explore the reactivity inside the misfolded and aggregated proteins. Recently, the Hong and Hatters group first demonstrated that unfolded proteomes can be targeted by globally labeling the exposed cysteine residues via maleimide chemistry and AIEgens upon stress-induced proteome unfolding in live cells. , Echoing Hong’s discovery, our group revealed that cysteine thiols were generally activated upon protein aggregation and can be covalently labeled by 1,4-Michael addition using a color-switch probe .…”
Section: Introductionmentioning
confidence: 99%